2016
DOI: 10.4238/gmr.15026343
|View full text |Cite
|
Sign up to set email alerts
|

Description of the diploid chromosome set of Triatoma pintodiasi (Hemiptera, Triatominae)

Abstract: ABSTRACT. Triatoma pintodiasi has been described and recently grouped in the Rubrovaria subcomplex. T. pintodiasi was initially compared to T. carcavalloi by staining and subsequently identified as T. circummaculata. However, after thorough examination, it was observed to be a cryptic species of T. circummaculata, and was described based on morphological features, morphometric data, and biochemical patterns of hemolymph. Thus, this paper aims to describe the karyotype of, and spermatogenesis in, T. pintodiasi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…To date, 150 species in 18 genera have been described (Alevi et al, 2015a). The importance of the triatomines in parasitology is due to these insects being transmitters of the etiologic agent of Chagas disease, Trypanosoma cruzi (Kinetoplastida, Trypanosomatidae) (Tavares and Azeredo-Oliveira, 1996), a flagellate parasite that infects many mammals, including humans (Dias, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…To date, 150 species in 18 genera have been described (Alevi et al, 2015a). The importance of the triatomines in parasitology is due to these insects being transmitters of the etiologic agent of Chagas disease, Trypanosoma cruzi (Kinetoplastida, Trypanosomatidae) (Tavares and Azeredo-Oliveira, 1996), a flagellate parasite that infects many mammals, including humans (Dias, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Heteroptera subfamily is composed of 150 species, grouped into 18 genera and six tribes (Alevi et al, 2015a), with all species being potential vectors of Chagas disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies on meiotic behavior 2 and characterization of nymphs 6 showed significant differences between T. pintodiasi and other species of the T. rubrovaria subcomplex. However, new comparative analyses were encouraged.…”
mentioning
confidence: 99%
“…However, new comparative analyses were encouraged. 2,5 Thus, this study characterized the genetic distance between the mitochondrial 16S rDNA gene of T. pintodiasi and that of the members of the T. rubrovaria subcomplex to evaluate the specific status of T. pintodiasi.…”
mentioning
confidence: 99%
See 1 more Smart Citation